Predictors of Occupational Stress in Manufacturing Industries - Dr. Sajid Mahmood Alvi; Sameena Humayoun Khan; Saira Bano (Journal of Management Practices, Humanities and Social Sciences, 2021)
This study was conducted to examine the marital status, role of gender and organizational ownership in occupational stress in the employees of different manufacturing industries. Occupational Role Questionnaire was used to collect the information from the participants. Sample was comprised of one twenty participants from POF Wah Cantt, Taxila and different industries of Haripur Hattar. Data was collected through purposive sampling technique and hypotheses were analyzed by using t test and Regression. Hypotheses of this study were supported. The findings shows \ that female employees significantly scored high as compared to their male counterparts. On occupational stress scores of married workers were significantly high as compared to unmarried workers. On occupational stress scores of private sector workers significantly high as compared to public sector workers. Marital status was the most prominent, gender was the secondary important, and organizational ownership was the third important predictor of occupational stress among the employees in the industrial units. The understanding of marital status, role of gender and organizational ownership in occupational stress in industries made this study valuable. Stress management programs in the workplace can be conducted for helping female employees to cope with occupational stress. Private organizations also needed to increase incentives so that they can get rid from occupational stress.